Women working in Algerian society have multiple motives and renewed difficulties - Benkhaled, Djamel (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2022)
The political, social, and economic changes that the world has witnessed in recent times forced the majority of women staying at home to go out to work, especially women who have a university education level to meet and cover the needs and requirements of life necessary for the family, in line with the requirements of the times and difficult social conditions, this exit reflected on the husband And children, so he became a strong economic support for the family in light of the high cost of living. On the other hand, a woman’s work constituted harm to her children as negligence in raising them and not creating the appropriate atmosphere for them and then deviation or corruption, although she was able to achieve great successes in multiple fields in addition to achieving herself as a working woman and at the same time as a housewife. This success faced many problems, including work pressure, the nature of workers, and the long working hours, as work and success caused her psychological problems and physical exhaustion, which was reflected on her family on the one hand, and on her professional and social returns on the other hand. In addition to all of this, the woman’s work has become the largest of marital disputes, due to the increased responsibility on her shoulders, even though she is considered a great source of income in increasing family welfare and securing her financial level. Accordingly, many individuals view women’s work negatively, forgetting that it greatly contributes to the development of societies, and that Her work personally benefits Her and Her children and husband and improves their standard of living, and That the woman who works feels confident in herself, and Is able to make her decisions more independently and without Exerting pressure and influence-t-on Her by others, and protecting Her from economic blackmail, because working women feel self-reliant. Work gives women material and moral strength, and helps them secure their requirements without having to ask for any help from others, and this enhances their strength Even more.